2012
DOI: 10.1111/j.1556-4029.2012.02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Classification of Age by Third Molar Development: The Use of Soft Evidence

Abstract: :  This study introduces a method to classify individuals according to an age threshold, given sex and third molars’ dental maturity measured on the Demirjian scale by expressing uncertainty on dental evidence (soft evidence). We introduced a procedure to learn the parameters of the Naïve Bayes model, and we discussed two classification rules. The model was estimated and tested on 559 Italians aged 16–22. Two experts provided the dental evaluations, and the model was estimated for each of them. We evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
(41 reference statements)
0
22
1
Order By: Relevance
“…Depending on the different legal requirements, such parameters can be set above 90% probability for criminal matters and from 51% to civil matters. 29 For forensic purposes, it is important that the test shows positivity in a low proportion of individuals under 18 years of age, which is more likely of having a false positive rather than a false negative. 9,25 This opinion is shared by other authors 15,28 because technically inacceptable mistakes e false negatives e lead to a more beneficial criminal treatment; technically unethical errors e false positives e lead to the violation of the minor's rights.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the different legal requirements, such parameters can be set above 90% probability for criminal matters and from 51% to civil matters. 29 For forensic purposes, it is important that the test shows positivity in a low proportion of individuals under 18 years of age, which is more likely of having a false positive rather than a false negative. 9,25 This opinion is shared by other authors 15,28 because technically inacceptable mistakes e false negatives e lead to a more beneficial criminal treatment; technically unethical errors e false positives e lead to the violation of the minor's rights.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of R (on the application of ZM and SK) v The London Borough of Croydon (Dental age assessment) [2016] UKUT 00559 (IAC), the court found that: “The fact that all teeth are mature in the sense that all have reached Demirjian stage H is a sign of chronological maturity but is not a reliable indicator of whether an individual is more or less than 18 years old.” This quote confuses chronological maturity with biological maturity, but in any event it recognizes the problem of using dental development in evidentiary settings. Outside of the courts, using dental formation in an evidentiary setting for problems that involve assessing whether an individual is above, or in some cases below, a particular age threshold has received considerable recent interest in the literature. However, there is neither consensus on what methods to use, nor uniformity of opinion on whether or not the dentition is informative enough to be used in age threshold determinations.…”
Section: Average Age‐within‐stage Is a Biased Estimator For The Averamentioning
confidence: 99%
“…Dental formation was scored by the third author following Moorrees et al (23) as follows: (1) no cusp formation (including no crypt formation), (2) cusp initiation, (3) cusp coalescence, (4) cusp occlusal outline complete, (5). crown half complete, (6) crown three-quarters complete, (7) crown complete, (8) root initiation, (9) root cleft initiation, (10) root one-quarter complete, (11) root half complete, (12) root threequarters complete, (13) root complete, (14) root apex half complete, and (15) root apex complete. In the original scoring lack of crypt formation was scored as 0 and crypt formation as 1.…”
Section: Reference Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It is a lifelong process that begins at the end of dental calcification (5,6) and causes a progressive narrowing of the pulp chamber volume of all teeth, although the rate of such narrowing varies according to the different tooth positions and types. Secondary dentin deposition should thus be considered an uneven biological process (4,7).…”
Section: Introduction and Aim Of The Researchmentioning
confidence: 99%